Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem Based Learning (PBL) Kelas IV SD - Harnofri Syafrihadi; Muhammadi Muhammadi (Universitas Negeri Padang, 2021)
This study aims to describe the increase in student learning results on thematic Integrated Learning Model using Problem Based Learning in class IV SDN 27 Salibawan Feed a town of Lubuk Sikaping. This research used a qualitative and quantitative approach. This type of research i.e. Research Action class (PTK). The subject of research is the grade IV SDN 27 Salibawan City Lubuk Sikaping Feed as many as 22 students. Research conducted two cycles. The design of the research include, (1) planning, (2) implementation, (3) and (4) observation of the reflection. The results showed an increase in: a) the RPP cycle I 85.93% Cycle II (SB) 100% (SB) b) implementation on aspect of teacher cycle I 85.71% (SB), a cycle II 100% (SB) c) Implementation on aspect students cycle I 85.71% (B) and Cycle II 100% (SB) d) student learning outcomes s iklus I 75.16 Cycle (B), II (A) 90.22. Thus the model of Problem Based Learning can improve the learning results of integrated thematic grade IV SDN 27 Salibawan City Lubuk Sikaping.